Doing youth participatory action research (YPAR) with Bourdieu: An invitation to reflexive (participatory) sociology - Larkins, Cath; Roy, Alastair; 2024; Kennelly, Jacqueline (The Sociological Review, 2024)
Recent years have seen an increased epistemological and methodological interest within sociology in participatory research. Seen as one mode by which to upturn the apparent antagonism between'town' and'gown', and as a pragmatic way to render sociology more'public', participatory research seems to offer resolutions to some of the field's more pressing recent concerns. It also appears to provide redress to continuing institutional pressure to establish'impact' for our research. This article offers a close and theoretically informed examination of the assumptions and practices of youth participatory action research, or YPAR, in order to contribute to deepened disciplinary understandings of the possibilities and limits of participatory approaches. Framed by the reflexive sociology of Pierre Bourdieu, we draw upon cross-national conversations through which we have intentionally reflected on moments of ambivalence or discomfort in our own participatory research practice(s). We utilise these to engage critically with some recurring problems in YPAR, suggesting these also have relevance to sociological enquiry more broadly. Our collaborative process of mutual reflexivity, developed through walking and talking together, writing individually and then providing feedback and clarifications, has allowed us to deepen our understanding of the power dynamics at play in participatory sociological enquiry.
Keywords: Collaborative Research; Community-based Research; Methodologies; Ambivalence